Graph the equation Y = 4x – 3

Question

Asked 11/13/2011 8:00:57 PM

Updated 3/14/2012 8:14:11 AM

1 Answer/Comment

shifa saleheen|Points 7424|

ephraimzRN|Points 998|

Expert answered|jameshand|Points 287|

Question

Asked 11/13/2011 8:00:57 PM

Updated 3/14/2012 8:14:11 AM

1 Answer/Comment

Rating

3

5(x+3)=7(x–5) solve for x

5x+15 = 7x -35

5x-7x = -15-35

-2x = -50

x = 25

5x+15 = 7x -35

5x-7x = -15-35

-2x = -50

x = 25

Added 3/14/2012 8:14:11 AM

This answer has been confirmed as correct and helpful.

Confirmed by andrewpallarca [6/16/2014 12:28:23 PM]

3x – 1 – x = 3x + 5

Question

Expert Answered

Updated 5/13/2014 4:15:54 AM

1 Answer/Comment

3x – 1 – x = 3x + 5;

2x - 1 = 3x + 5;

2x - 3x = 5 + 1;

-x = 6;

x = -6

2x - 1 = 3x + 5;

2x - 3x = 5 + 1;

-x = 6;

x = -6

Added 5/13/2014 4:15:49 AM

This answer has been confirmed as correct and helpful.

5(x + 3)=7(x – 5)

Question

Expert Answered

Updated 11/13/2011 8:17:41 PM

2 Answers/Comments

The answer to the equation: 5(x + 3)=7(x – 5) is to rewrite the equation as 5x + 15=7x – 35 and then adding like variables: 50=2x and then solving for x which is x=25.

Added 11/13/2011 8:17:41 PM

This answer has been confirmed as correct and helpful.

Confirmed by andrewpallarca [7/1/2014 1:25:45 PM]

27,211,398

questions answered

There are no comments.